„Eli, Eli, lema sabachthani” (Mt 27,46). Aramejskie wyrażenia w greckim tekście Nowego Testamentu - Ostański, Piotr (Poznańskie Studia Teologiczne, 2016)
There is no doubt that in Jesus’ times the three ancient languages, Hebrew, Aramaic, and Greek were commonly spoken in Roman Palestine. It is also beyond discussion that Jesus’ mother tongue was Aramaic. There are many Aramaic wordings in the Greek New Testament that are hinting at the original language of Jesus’ sermons. The aim of this paper is to investigate three Aramaic phrases in the Greek Gospels: Jesus’ cry from the cross (Eli, Eli, lema sabachthani?; Mt 27:46; Mk 15:34), his command to the daughter of Jairus (Talitha koum; Mk 5:41) and his allusion to Aramaic characters (iōta – keraia; Mt 5:18). Furthermore, there are also many Aramaic common words and proper names (personal and place names) in the Greek New Testament. They will require an extra future research.